Sasakian manifolds satisfying certain conditions on Q tensor - YILMAZ, HÜLYA (SPRINGER BASEL AG, 2020)
The object of the present work is to investigate Sasakian manifolds satisfying certain conditions on Q tensor whose trace is well-known Z tensor.
Keywords: Sasakian manifold; Q tensor; Unit sphere; Weyl conformal curvature tensor field; Projective curvature tensor field